A procedure for writing the social impact of a result in Higher Education - Martínez Escoda, Erenia de la Caridad; Pino Estévez, Pedro Ramón; Santacana Palencia, Teresita Avelina (Transformación, 2024)
Objective: This paper aims at describing a procedure for writing relevant findings of educational research in Higher Education processes. Methods: From the dialectical materialist perspective, a systematization of the references related to the notion of impact, social impact, cause and effect relationship, and classification of relevant findings was undertaken. This systematization using analysis, synthesis, induction, deduction and abstraction concretion, among others, lead to describe the foundations of finding relevance description higher education research. The sample comprises 25 self-assessment reports belonging to 20 majors, four study centers and the institution general report. Results: A procedure for writing the social impact of a result in Higher Education is the main finding. The proposed procedure takes into consideration the social impact arising from the results presentation, its social relevance, significance for Higher Education processes, and structural components. Conclusions: The procedure herein described favors the comprehension of research findings social relevance.
Keywords: Educational research; higher education; relevance; quality of education